Pricing Strategies of Ambo Mineral Water from Producer and Sellers Perspectives’ - Etana, Negash Geleta (International Journal of Marketing Research Innovation, 2020)
The study was conducted on “Pricing strategies of Ambo Mineral Water from producers and sellers’ perspectives’’ and a data was collected from sellers of Ambo Town West Shoa Zone Oromia Regional State. The main objective of the study is to see the pricing strategies of Ambo Mineral Water and the scope is delimited to sellers of Ambo Mineral Water found in Ambo Town. The sample size was determined based on the maturity strategies which more used when the responses of the respondents are redundant. Accordingly, the study is used sample size up to 54 to see the facts. To analyze the collected data the study used descriptive statistics for all parties of the study. The last section presents the conclusions and recommendations directed to the respondents. In conclusion, all the respondents have one or two pricing strategies and this implies that the respondents have more knowledge on the pricing strategies. Therefore, it is more essential to recommend all the respondents must have the right pricing strategies according to their offerings based on the customers’ sensitivity.